Influence of dietary roughage level and Megasphaera elsdenii on feedlot performance and carcass composition of thin cull beef cows fed for a lean market - DeClerck, Jonathan C (Transl Anim Sci, 2019)
One hundred forty-four cull cows (body condition score = 2.10 ± 0.61; BW = 456 ± 47 kg) were organized into a 2 × 2 factorial design (48 pens, 12 pens/treatment, and 3 cows/pen) to evaluate the effect of dietary roughage level and oral drenching of Megasphaera elsdenii NCIMB 41125 (M. elsdenii culture; Lactipro Advance; MS Biotec Inc., Wamego, KS) on performance and carcass characteristics. Cattle were finished over a 42-day realimentation period, and aggressively stepped up over a 10-day period to either a high roughage finisher (HRF; 25% roughage) or a low roughage finisher (LRF; 10% roughage). Within diet, cattle were administered no probiotic or 100 mL of M. elsdenii culture (M. elsdenii NCIMB 41125, 2 10(8) cfu/mL) on day 0. No diet × probiotic interactions were detected (P ≥ 0.15), suggesting that the magnitude of the response was not influenced by the concentrate level of the diet. The main effect of diet triggered several significant responses. Decreasing roughage level tended to improve average daily gain (ADG) by 9.7% (0.26 kg, P = 0.08), while decreasing dry matter intake (DMI) by 0.9 kg (P = 0.09), provoking a 19.7% enhancement of feed efficiency (0.036 units, P < 0.01). However, interim data revealed declines of performance parameters among both diets with a significant difference between treatments only documented during the final phase of the realimentation period. During the final 14 days, LRF posted a 0.68 kg increase in ADG (P = 0.05) and a 2.0 kg decrease in DMI (P = 0.01), translating to improved feed efficiency (0.054 units, P = 0.03). This suggests that increasing the caloric density of finishing diets may help offset the regression of performance typically observed following a compensatory gain. No carcass traits were impacted by either diet or M. elsdenii culture (P ≥ 0.08). Overall, oral drenching of M. elsdenii culture tended to augment ADG (0.26 kg, P = 0.08) and carcass ADG (0.20 kg, P = 0.10). Implying that M. elsdenii culture was effective at alleviating the acidosis risk prompted by the rapid step-up period employed in the trial and may help capitalize on the narrow timeline of compensatory gain in cull cow realimentation.